Association between psychological capital and depressive symptoms during COVID-19: The mediating role of perceived social support and the moderating effect of employment pressure - Huang, Yalian; Lin, Xin; Yang, Jian; Bai, Hefei; Tang, Ping; Yuan, Guangzhe Frank (Frontiers in Public Health, 2023)
Introduction The Coronavirus Disease 2019 (COVID-19) pandemic affects individuals' mental health that can result in fear of getting COVID-19 infection and depression. Prior research has demonstrated that both psychological capital and perceived social support are related to the severity of depression. Yet no study explored the direction of associations between these factors. This undermines the validity of psychological capital as a basis for health interventions. Methods This study aimed to explore the association between psychological capital, perceived social support, employment pressure, and depressive symptoms during COVID-19. A cross-sectional design was employed in a sample of 708 Chinese senior medical students who were asked to complete an online questionnaire survey. Results Results indicated that psychological capital negatively predicts depressive symptoms (β = −0.55, p < 0.001); perceived social support plays a mediating role in the impact of psychological capital on depressive symptoms (indirect = −0.11, SE = 0.02, p < 0.001, 95%CI [−0.16, −0.07]), and these associations were moderated by employment pressure. Medical students with high employment pressure, the negative impact of psychological capital on depressive symptoms was statistically significant (β = −0.37, SE = 0.05, p < 0.001, 95% CI [−0.046, −0.27]); when the perceived employment pressure was low, the negative effect of psychological capital on depressive symptoms, although significant, was stronger (β = −0.49, SE = 0.04, p < 0.001, 95% CI [−0.57, −0.40]). Discussion The current study highlights that it is of great significance to address Chinese medical students' employment pressure and improve their mental health during the COVID-19 epidemic.